PERBANDINGAN PENGARUH TEKNIK RELAKSASI NAFAS DALAM DAN ORIENTASI LINGKUNGAN TERHADAP TINGKAT KECEMASAN ANAK SEBELUM PENCABUTAN GIGI - Hernita, Rifa; Amir, Yufitriana; Nopriadi, Nopriadi (Jurnal Keperawatan Profesional, 2022)
Background: Anxiety is an unpleasant feeling that is felt by someone when they are in an uncertain condition so that it is said to be anxiety. This study aims to compare the effect of deep breathing relaxation techniques and environmental orientation on children's anxiety levels before tooth extraction. Methods: This study used a quasi-experimental research design using the pretest-posttest non-equivalent control group method. The measuring instrument used is the Modified Dental Anxiety Scale (MDAS) Questionnaire. Using the Wilcoxon and Mann Whitney test. Results: The results of the univariate analysis showed that the majority of respondents aged 6 years were 19 (55.9%), and the majority of the respondents were female respondents as many as 22 (64.7). Environmental orientation affects children's anxiety levels with p value (0.001) < (0.05), deep breathing relaxation techniques affect children's anxiety levels with p value (0.005) < (0.05). The effect of the orientation of deep breathing relaxation techniques and environmental orientation results of bivariate analysis using Mann Whitney p value (0.170) means that there is no difference between groups 1 and 2 Conclusion: The results of this study recommend the dental health department in order to reduce children's anxiety when they want to do tooth extraction using the intervention of deep breathing relaxation techniques and environmental orientation.